Implementation of Greenhouse Technology as an Adaptation Solution to Climate Change in Subtropical Regions - Timo Sonita; Lira Muhardi; Eni Karningsih (CV. HEI PUBLISHING INDONESIA, 2024)
The implementation of greenhouse technology as an adaptation solution to climate change in subtropical regions is becoming increasingly important given the increasingly felt impacts of climate change. This article explores the concepts, benefits, and challenges of implementing greenhouse technology as an adaptation measure in subtropical areas. Through a comprehensive literature review, we present an analysis of the effectiveness of greenhouse technology in reducing the impacts of climate change, increasing water availability, and enhancing crop productivity. We also discuss the social, economic, and environmental implications of implementing this technology in subtropical regions. The findings from this research provide valuable insights for practitioners, researchers, and policymakers in understanding the potential of greenhouse technology as a sustainable adaptation solution in subtropical areas